Pemanfaatan Bekas Adukan Mortar pada Pratikum Batu (Masonry) untuk Paving Block - Saryeni Maliar -; Bakhri - - (Jurnal Ilmiah Poli Rekayasa, 2017)
Stone Construction Laboratory is one of the existing courses in the Department of Civil Engineering Polytechnic State of Padang. Students are required to practice firsthand the theories about stone construction that have been studied. Stone work or often called masonry is wall or brick installation work for floor, wall, or fence. In practicum stone, the material used is artificial stone like brick and can also natural stone by using an adhesive substance usually known by the name of spesi or mortar.Mortar or spesi is one of the building materials that serves to glue the pairs of bricks, brick, stucco and so on. Mortars consist of sand, cement and water. In a stone work practicum where the work is not permanent (unloading pairs) then the cement material is replaced by lime which is a temporary binder. So far, the rest of the mortar use for the stone practicum is just thrown away because it cannot be used anymore, therefore it takes alternative utilization of the former mortar, for that the author tries to research by using it to make paving blocks. Paving blocks or concrete bricks for floors are a component of building material made from a mixture of hydraulic cement or the like, aggregates and water with or without other additives which do not reduce the quality of the paving blockThe study used comparison between paving block with mixed composition of mortar, cement and water mixture and paving block with standard mixture composition ie cement, sand and water. Paving is made by pressing using hydraulic press machine with a compressive strength of 25 kg and compressive strength testing with Universal Testing Machine.Based on the results of the research, it was found that the paving block from the utilization of mortar has a compressive strength higher than the standard paving block. At the age of 14 days, the compressive strength of the paving block from the utilization of mortar used has a compressive strength of 76.14 kg